Guidance Note for the Use of Third-Party Indicators in Fund Reports. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2018)
This note provides guidance on use of third-party indicators (TPIs) in Fund reports, in line with the policy endorsed by the Board in November 2017.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: El Salvador